2007
DOI: 10.1007/s11896-007-9011-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Officer and Agency Characteristics on the Likelihood of Arrest in Domestic Violence Situations among Rural Law Enforcement Officers

Abstract: Domestic violence cuts across all demographic groups. The factors related to why police officers arrest in some domestic violence situations but not others have been often studied. Little research, however, has been conducted on the arrest views of rural police officers. One hundred seventy line officers in six rural Midwestern counties were surveyed to determine the impact of officer personal characteristics and agency type on arrest decisions in various hypothetical domestic violence scenarios. First, the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Scholars [18,26,[30][31][32] found officer demographic information as having an influence on arrest decision-making. Some scholars found that female police officers are less likely to make an arrest than male officers [26], and those with few years of experience have high likelihood of making an arrest compared to more experienced police officers [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars [18,26,[30][31][32] found officer demographic information as having an influence on arrest decision-making. Some scholars found that female police officers are less likely to make an arrest than male officers [26], and those with few years of experience have high likelihood of making an arrest compared to more experienced police officers [30].…”
Section: Literature Reviewmentioning
confidence: 99%